The effect of stranded marine debris on the mangrove ecosystem in the coastal area of Liquiça Municipality of Timor-Leste - Santos, Alzira de Jesus dos; Damar, Ario; Hariyadi, Sigid; Fonseca, Abilio da (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
This study aims to determine the types, abundance and composition of the stranded marine debris and its impact on the mangrove ecosystem in Liquiça Municipality, Timor-Leste. Data were collected from 6 September 2024 to 30 October 2024 at three stations using surveys and direct field observations. Analysis was conducted both quantitatively and qualitatively. Seven types of debris were identified : plastic, metal, glass, rubber, fabric, organic and other inorganic waste. Plastic was the most dominant at all stations, Station 1 recorded the highest debris abundance at 1.62 items/m², with plastic waste also dominating by category at Stations 1 and 3 (155 items/m² and 137 items/m²). Station 1 also had the heaviest debris weight at 4,339 g/m² and the largest volume at 235 cm³/m². The findings indicate that stranded marine debris does have a negative impact on the mangrove ecosystem, significant negative correlation between the weight of marine debris and macrozoobenthos. However no correlation between debris and mangrove’s seedlings was found.